Cognitive-behavioral and dietary weight loss intervention in adult kidney transplant recipients with overweight and obesity: Results of a pilot RCT study (Adi-KTx) - Barchfeld, Dana Coco; Vagi, Ricarda-Katharina; Lüdtke, Katrin; Schieffer, Elisabeth; Güler, Faikah; Einecke, Gunilla; Jäger, Burkard; de Zwaan, Martina; Nöhre, Mariel (Frontiers in Psychiatry, 2023)
The obesity epidemic and its health consequences have not spared the population of kidney transplant (KTx) candidates and recipients. In addition, KTx recipients are susceptible to weight gain after transplantation. Overweight and obesity after KTx are strongly associated with adverse outcomes. Therefore, we designed a randomized controlled, mono-center study to specifically test the effectiveness of a primarily cognitive-behavioral approach supplemented by nutritional counseling for weight reduction following KTx as the intervention group (IG) in comparison to a brief self-guided intervention as control group (CG). The study was registered in the German Clinical Trials Register (DRKS-ID: DRKS00017226). Fifty-six KTx patients with a BMI from 27 to 40 kg/m2 were included in this study and randomized to the IG or CG. Main outcome was the number of participants achieving a 5% weight loss during the treatment phase. Additionally, participants were assessed 6 and 12 months after the end of the 6-month treatment phase. Participants significantly lost weight without group differences. 32.0% (n = 8) of the patients in the IG and 16.7% (n = 4) of the patients in the CG achieved a weight loss of 5% or more. Weight loss was largely maintained during follow-up. Retention and acceptance rate in the IG was high, with 25 (out of 28) patients completing all 12 sessions and one patient completing 11 sessions. Short-term, cognitive-behaviorally oriented weight loss treatment seems to be feasible and acceptable for patients after KTx who suffer from overweight or obesity. This clinical trial was ongoing at the onset of the COVID-19 pandemic which might have influenced study conduct and results. Clinical Trial Registration: https://clinicaltrials.gov/ DRKS-ID: DRKS00017226.